Catchalls and Conundrums: Theorizing “Sexual Minority” in Social, Cultural, and Political Contexts - Mizzi, Robert C.; Walton, Gerald (Paideusis, 2014)
The term “sexual minority” functions in social, cultural, and political contexts as a catchall for minority sexuality categories. Yet, apart from serving as an umbrella term, its uses are contradictory. On the one hand, the term emphasizes “sexuality,” which serves the purposes of religious fundamentalist and political groups that demonize minority sexualities to the exclusion of identity, background or family status. On the other hand, the term can be useful for readers and researchers in sexuality studies to become more globally aware of, and to reconceptualize, sexuality outside of tightly contained LGBT boxes. Such a contradiction has implications for education practice and policy. We suggest, for instance, using the term cautiously when describing same-sex sexualities because, as an umbrella term, it can homogenize people who represent a highly diverse spectrum of racialized categories, class backgrounds, genders, sexualities, and other social markers of difference. As a pedagogical heuristic device, the term is useful in delineating the differences between queer and sexual minority pedagogies when deciding upon the approach that will best draw an audience into the discussion. Our overall goal through this critical exploration is to support new understandings and insights of sexual diversity in ways that effectively challenge heterosexism and homophobia.